Antenna Array Construction Synthesis - V. V. Nikitin; A. D. Frantsuzov (Известия высших учебных заведений России: Радиоэлектроника)
The problem of linear antenna construction synthesize is first formulated and solved. Linear antenna consists of antenna array (AR) and power divider (PD). Linear omnidirectional AR with cosecant pattern is synthesized using partial-beam method. Beam-forming scheme for this antenna is based on two directional unequal splitters. The article proposes itera-tive method considering AR and beam-forming scheme mutual effect in terms of scattering matrix. Synthesis results demonstrate rapid convergence of the process and provide optimal pattern.